Evaluation of the suitability of responses on various organisational levels in terrestrial Oligochaeta to determine species sensitivity relationships - Fourie, Frana (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.